EXPLORING ANXIETY LEVELS AMONG VOLLEYBALL PLAYERS IN JAMMU & KASHMIR: AN ANALYTICAL INVESTIGATION - Farhat Ayoub; Jaswinder Singh (CV. RADJA PUBLIKA, 2024)
Anxiety is a prevalent psychological phenomenon that significantly impacts sports performance. This research paper delves into the exploration of anxiety levels among volleyball players in the region of Jammu & Kashmir, aiming to understand the factors contributing to anxiety and its implications on players’ performance. A mixed-methods approach was adopted, combining quantitative surveys and qualitative interviews. Findings reveal varying levels of anxiety among players, influenced by factors such as competition pressure, societal expectations, and personal coping mechanisms. The paper concludes with recommendations for interventions and strategies to mitigate anxiety and enhance players’ mental well-being in the context of competitive sports.